Maintenance of Remission with Partial Enteral Nutrition Therapy in Pediatric Crohn’s Disease: A Retrospective Study - Jacqueline M. Schulman; Liat Pritzker; Ron Shaoul (Canadian Journal of Gastroenterology and Hepatology)
Background. Partial enteral nutrition (PEN) may be helpful for the maintenance of remission in pediatric Crohn’s disease patients. Aims. To evaluate the efficacy of PEN treatment for preventing clinical relapse. Methods. We retrospectively assessed 42 pediatric Crohn’s disease patients who entered clinical remission on 4–12 weeks of exclusive enteral nutrition (EEN) and were maintained on PEN as a supplementary diet. We evaluated the efficacy of the treatment at different time points using the weighted Pediatric Crohn Disease Activity Index (wPCDAI), Physician Global Assessment, laboratory parameters, and growth of each patient. Additionally, we assessed the use of concomitant medications. Results. The median length of remission with PEN was 6 (0–36) months. Patients’ remission was maintained on PEN without concomitant medications for a median time of zero months (0–16). The mean body mass index in the PEN group increased from 18.1 to 18.8 after six months of PEN. The median wPCDAI decreased from 30 at diagnosis to 5.0 after EEN and increased to 7.5 after three months of PEN. Overall, the median wPCDAI decreased by 26.2. Conclusions. PEN treatment was partially effective in maintaining remission and was able to increase BMI and lower wPCDAI. Most patients required concomitant medication after PEN initiation.